The determinants of under-5 age children malnutrition and the differences in the distribution of stunting-A study from Armenia. - Pavitra Paul; Bhanu Arra; Mihran Hakobyan; Marine G Hovhannisyan; Jussi Kauhanen (PLoS ONE)
Stunting undermines economic growth by perpetuating the vicious cycle of poverty and labour market performance. Studies have captured the trend in stunting and present distributional evidence of policy effects in the country contexts. We identify the determinants of U5 (under 5 years of age) malnutrition for the poor and the Nonpoor and compare the distribution of stunting at four time points (2000, 2005, 2010 and 2015) over a 15-year period between different groups of population. Further, we decompose the gap in malnutrition into causes of differences in stunting between worse-off and better-off socioeconomic groups of the population and estimate the magnitude of distributional differences in stunting between two socioeconomic groups. We also present the inequality trend over time that provides insights into the dynamicity of the effect of different determinants on stunting at different time points. Using 35,490 observations from Armenian Demographic and Health Survey Data [four waves: Year2015,9533; Year2010,8644; Year2005,8919; Year2000,8334], we apply regression-based decomposition method and inequality measures to identify the determinants of malnutrition and distribution of stunting between and within socioeconomic groups. Although the proportional difference in prevalence of stunting between worse-off and better-off children of 13 months and above are reduced by 9.5% in 2015 compared to 2000, the association between socioeconomic position and stunting is statistically significant among children aged 13 months and above in 2000, as well as among children of 36 months and above in 2015. This study demonstrates that the less of socioeconomic distribution of the population, but rather more of the effect from in-country region and settlement of residence are significantly associated with stunting. The approach of our analysis is potentially also a useful tool to generate evidence for decision making towards achieving SDGs 2.2. We conclude that development in childhood is not independent from the distributional effect of region specific development initiatives. Understanding the regional characteristics and resources allocated for the maternal and child health is the necessity to address stunting.